GOJEK DAN STUDI FENOMENOLOGI SPONSORSHIP DI LIGA INDONESIA - Pasaribu, Pilemon; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2018)
Recently, the promotion using sponsorship is becoming continuous in Indonesian football. This is evident from the number of sponsors who entered the league and club sponsor. The promotion using sponsorship should be evaluated whether it has a significant impact on brand awareness of sponsors and then followed by increase the purchasing intention of sponsor’s products. The purpose of this study is to analyze the impact of sponsorship activities by Gojek on brand awareness of sponsor by PSIS supporters and how it affects purchasing intention of go -ride by supporters.The method used is qualitative method with phenomenology study approach, where the data collection is done by interview, observation, and document ation. This method is chosen to mak e the research in-depth and get accurate results. The sampling technique in this research using purposive and snowballing sampling techniques.The results of this study showed that sponsorship by Gojek has a positive effect on brand awareness of sponsors. In addition, a high awareness of sponsorship brands increases the purchasing intention toward go -ride by supporters.